0
$\begingroup$

I want to solve $$ (1 - 2\lambda + \lambda^2)(1 - \lambda) + 2 - 3(1 - \lambda) = 0 $$ Eventually I would probably want to factor the polynomial, but I don't know how to multiply the parentheses of the polynomial's first part.

$\endgroup$
2
$\begingroup$

$$(a+b+c)(d+e)=a(d+e)+b(d+e)+c(d+e)$$


Note that $1-2\lambda +\lambda^2=(1-\lambda)^2$ and set $1-\lambda=X$ to get $$X^3-3X+2=0$$ Now it should be easy to find a solution $X=1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.